ASSESSING HEALTH CARE PROVIDERS' PERSPECTIVES ABOUT ADVANCE DIRECTIVES AT TERTIARY CARE HOSPITAL: A QUANTITATIVE CROSS-SECTIONAL STUDY (The Research of Medical Science Review, 2025)
Background: Advance directives (AD) are medical-legal documents that outline a patient's preferences regarding healthcare when the person is not competent to make decisions. Its application and understanding among healthcare providers are important but remained underexplored in Pakistan. Purpose: The purpose of this study was to assess the level of knowledge and attitudes of healthcare providers toward advance directives at a tertiary care hospital in Karachi, Pakistan. Method: A cross-sectional survey was conducted with 306 healthcare providers, including nurses and physicians, across various specialties. Knowledge and attitudes toward ADs were assessed using a structured questionnaire. Chi-square tests were used to examine associations between participants' characteristics and their knowledge and attitudes.Finding(s): The majority of participants (73.9%) demonstrated adequate knowledge about ADs, while 79.4% exhibited positive attitudes. Older and more experienced healthcare providers were more likely to have positive attitudes toward ADs. Despite high overall knowledge, there were gaps, particularly in understanding specific types of ADs and their applications. The study found no statistically significant associations between knowledge.